The economics of heritage and tourism (Cadernos de Sociomuseologia, 2016)
Tourism has been studied as an economic activity, from their products and businesses activities. But why are travelling peoples and for what? What’s happen in the tourism world under the iron hand of the modern market, analysed from the both sides, demand and offer, with the emergence of the society of knowledge and information, with their new middle class growing with more education and culture, a young people predisposed to the e-learning and a increasing segment of tourists who anticipate the middle-aged and retire? A new conceptual research framework emerges and a new tourism paradigm: Environmental Tourism (Cultural tourism and tourism of nature). This paper wants to discuss the connection between heritage and tourism economy. Researching how is create and reproduced the capital of tourism and recognising the cultural values and products penetration in the tourism activity, in the framework of the changing taste (preferences) and ethical values of middle class.Keywords: Taste. Cultural tourism. Externalities